Transformasi Pendidikan Karakter: Solusi Cegah Bullying dan Tawuran di SDN Karangjaya Kabupaten Sukabumi: Pengabdian - Jimatul Arrobi; Neng Rani Fauziyah; Selpi Apriyanti; Ardhiva Fachrul Adji; Rani Siti Ranisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The community service program at SDN Karangjaya, Sukabumi, focused on preventing bullying and conflict between students through character education transformation. The Participatory Action Research (PAR) method was used by involving teachers, students, and parents in identifying problems, planning, implementing, and evaluating the program. Activities included teacher training, student coaching through extracurricular activities, and anti-bullying campaigns. The results showed a decrease in verbal bullying from 28% to 15% and student fights from 12% to 5%. Teachers were more skilled at integrating character values ​​into learning, students increased their awareness of the importance of mutual respect, and parents were more active in accompanying their children. This program proves that character education transformation is effective as a preventive approach to creating a peaceful, child-friendly, and violence-free school culture.